Implications of Company Size, Company Growth, Institutional Ownership, Profitability and Previous Audit Opinions on Going Concern Audit Acceptance - Joni Hendra; R Hery Koeshardjono; Heny Herawati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The objectives to be achieved in this study are: (1) to determine the implications of company size, company growth, institutional ownership, profitability and previous audit opinion on going concern audit opinion acceptance. (2) to determine the dominant implication of these variables on the acceptance of going concern audit opinion. The type of research used is quantitative with a causal associative approach. While the population in this study are mining companies listed on the Indonesia Stock Exchange in 2018-2020 with a sample of 10 companies taken by purposive sampling. The reason for this research is based on the consideration that there are still inconsistent results from previous studies. The results of research by Muslimah and Triyanto (2019) show that prior opinion has a significant effect on the acceptance of going concern audit opinions. While the company's growth, debt default, opinion shopping do not partially affect the acceptance of going concern audit opinion. According to Nurpatiw and Rahardjo (2014) there is an influence between company size, institutional ownership, on the tendency to accept going concern audit opinions. Research gives results that company size, institutional ownership, and previous audit opinions have significant implications for the acceptance of going-concern audit opinions, while company growth and profitability have no implications for the acceptance of going-concern audit opinions. The previous audit opinion has a dominant implication on the acceptance of going concern audit opinion.